Drying: A Practical Technology for Blueberries (Vaccinium corymbosum L.)—Processes and their Effects on Selected Health-Promoting Properties - Elsa Uribe; Antonio Vega-Galvez; Alexis Pasten; Kong Shun Ah-Hen; Nicol Mejias; Lorena Sepúlveda; Jacqueline Poblete; Luis S. Gomez-Perez (Antioxidants)
The global dried blueberry market is steadily growing, driven by the creation of innovative blueberry-based products. This trend presents an opportunity to explore a previously untapped segment of the blueberry market in Chile. In this study, a comprehensive assessment of four drying techniques (hot-air drying [HAD], vacuum drying [VD], infrared drying [IRD], and freeze-drying [FD]) was conducted to determine best operating conditions and preserve the health-promoting properties of blueberries. Drying kinetics, proximate composition, color, anthocyanin content, individual phenols, and antioxidant, antiproliferative, and antidiabetic potential of blueberries were evaluated. VD showed the highest drying rates, reaching equilibrium moisture more rapidly (Deff value of 3.44 × 10−10 m2/s). Drying caused an increase in lipid content but a decrease in protein content. The color parameter L* increased in all dried samples, and C* reflected color intensification. FD best retained anthocyanin content, which decreased significantly in the other drying processes. Chlorogenic acid and rutin predominated in HAD, IRD, and FD samples. The antioxidant potential in ORAC assays increased for all drying methods but decreased in DPPH assays. Blueberry extracts from FD and HAD exhibited the greatest antiproliferative effect against A549 and H1299 cell lines, respectively. HAD showed the best inhibitory effect on α-glucosidase, with an IC50 value of 0.276 mg/mL, similar to acarbose (IC50 = 0.253 mg/mL). Given the significant retention of health-promoting properties and bioactive compounds in HAD-dried samples, this method is advisable as a sustainable option for drying blueberries in Chile.